KESALAHAN BERBAHASA PEMELAJAR BIPA DI KBRI NEW DELHI (LANGUAGE ERROR OF BIPA STUDENTS IN KBRI NEW DELHI) - Lefrand Rurut (Balai Bahasa Sulawesi Utara, 2018)
The aims of this research are to (1) describe the types of language error which is done by the students who follow the BIPA program at Indonesian Embassy, New Delhi, India and (2) to elaborate the way to solve the language error problem which is done by the students who follow the BIPA program at Indonesian Embassy, New Delhi, India. This research use case study method. The collecting data procedure in this research is done by using observation method. The writer himself does the teaching program and the observation directly, then record the data.Based on the result of data analyses, it can be concluded that the types of language error which is done by the students of BIPA program in Indonesian Embassy, New Delhi India are (1) expressing error, (2) personal error, (3) group error, (4) analogy error, (5) teacher error. Besides, the students of BIPA program in Indonesian Embassy, New Delhi India make error on phonology, morphology, and syntax field. To solve those problems, the writer suggest that the teacher has to understand previously those student’s language errors, then allocating more time to give the proper comprehension to the students so that the language errors mentioned can be solved or at least can be minimalized.Moreover, to solve the student’s language error on phonological, morphological, and syntax, the writer suggest to the teacher to provide time or special class for especially learning grammar because commonly the learning modules or the materials of BIPA do not input the complete grammar material.This research contributes the important input to the BIPA teacher who will teach Indonesian language for Indian students. This research also to add the language knowledge especially in language error field.